Rare Cell Proteomic Reactor Applied to Stable Isotope Labeling by Amino Acids in Cell Culture (SILAC)-based Quantitative Proteomics Study of Human Embryonic Stem Cell Differentiation - Tian, Ruijun (The American Society for Biochemistry and Molecular Biology, 2011)
The molecular basis governing the differentiation of human embryonic stem cells (hESCs) remains largely unknown. Systems-level analysis by proteomics provides a unique approach to tackle this question. However, the requirement of a large number of cells for proteomics analysis (i.e. 10(6)–10(7) cells) makes this assay challenging, especially for the study of rare events during hESCs lineage specification. Here, a fully integrated proteomics sample processing and analysis platform, termed rare cell proteomic reactor (RCPR), was developed for large scale quantitative proteomics analysis of hESCs with ∼50,000 cells. hESCs were completely extracted by a defined lysis buffer, and all of the proteomics sample processing procedures, including protein preconcentration, reduction, alkylation, and digestion, were integrated into one single capillary column with a strong cation exchange monolith matrix. Furthermore, on-line two-dimensional LC-MS/MS analysis was performed directly using RCPR as the first dimension strong cation exchange column. 2,281 unique proteins were identified on this system using only 50,000 hESCs. For stable isotope labeling by amino acids in cell culture (SILAC)-based quantitative study, a ready-to-use and chemically defined medium and an in situ differentiation procedure were developed for complete SILAC labeling of hESCs with well characterized self-renewal and differentiation properties. Mesoderm-enriched differentiation was studied by RCPR using 50,000 hESCs, and 1,086 proteins were quantified with a minimum of two peptides per protein. Of these, 56 proteins exhibited significant changes during mesoderm-enriched differentiation, and eight proteins were demonstrated for the first time to be overexpressed during early mesoderm development. This work provides a new platform for the study of rare cells and in particular for further elucidating proteins that govern the mesoderm lineage specification of human pluripotent stem cells.